Development of Augmented Reality Interactive Comic Storybooks as Art History Learning Media for Early Age Children - Aruna, Alby; Roziqin, Mohamad Firzon Ainur; Qolbi, Muhammad Syifa'ul; Iriaji, Iriaji; Surya, Eka Putri; Marcelliantika, Adinda; Wijaya, Ginanjar Atma (Abdimas Indonesian Journal, 2024)
The development of an interactive comic book based on Augmented Reality (AR) as a learning medium for art history for early childhood aims to enhance children's interest and understanding of art history material. This program combines AR technology with educational content in comic form, allowing children to interact with visual and audio elements that support the art history narrative. The methods used include designing and developing comic content, implementing AR technology, and evaluating effectiveness through observation and user feedback. The results indicate a significant increase in children's learning interest and understanding of art history. The implementation of this learning medium is expected to support the cognitive and creative development of early childhood.